2019
DOI: 10.4110/in.2019.19.e28
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of IL-18 Expression in the Gut by Metformin-induced Gut Microbiota Modulation

Abstract: IL-18 is a crucial pro-inflammatory cytokine that mediates chronic intestinal inflammation. Metformin, an anti-diabetic drug, was reported to have ameliorative effects on inflammatory bowel disease. Recently, the mechanism of action of metformin was explained as a modulation of gut microbiota. In this study, fecal microbiota transplantation (FMT) using fecal material from metformin-treated mice was found to upregulate the expression of GLP-1 and pattern-recognition receptors TLR1 and TLR4 for the improvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…During the past years MET effects on inflammation have been the subject of many reports. Indeed, MET decreases cytokine levels in vascular cells [29] , experimental myocarditis [30] , sepsis [31] , gut inflammation [32] , interleukin (IL)-10 deficient mice [33] , lipopolysaccharide (LPS)-stimulated mouse colon cells [34] , metabolic syndrome induced by fructose [35] , PCOS [36] , and animals or patients with diabetes [37] . Interestingly, these effects of MET are independent of its antihyperglycaemic action [38] .…”
Section: A Rational Set Of Protective Mechanismsmentioning
confidence: 99%
“…During the past years MET effects on inflammation have been the subject of many reports. Indeed, MET decreases cytokine levels in vascular cells [29] , experimental myocarditis [30] , sepsis [31] , gut inflammation [32] , interleukin (IL)-10 deficient mice [33] , lipopolysaccharide (LPS)-stimulated mouse colon cells [34] , metabolic syndrome induced by fructose [35] , PCOS [36] , and animals or patients with diabetes [37] . Interestingly, these effects of MET are independent of its antihyperglycaemic action [38] .…”
Section: A Rational Set Of Protective Mechanismsmentioning
confidence: 99%
“…Decreased gut permeability limits the release of endotoxins such as LPS, which in turn improves the chronic low-grade inflammatory status and reduces vascular inflammation (Tang et al, 2019). A recent study showed that fecal microbiota transplantation (FMT) using fecal material from metformintreated mice can not only upregulate the expression of GLP-1 and pattern-recognition receptors TLR1 and TLR4 to improve hyperglycemia caused by a high-fat diet (HFD), but can also downregulate the expression of the inflammatory cytokine IL-18 (Lee et al, 2019) which has been identified as a possible risk factor for CVD (Jefferis et al, 2011). However, metformin treatment was recently found to be associated with an increased concentration of TMAO (a promoter of atherothrombotic disease) (Brown and Hazen, 2018;Croyal et al, 2020).…”
Section: The Effect Of Oral Hypoglycemic Drugs On Gut Microbiota Metfmentioning
confidence: 99%
“…The experiment also found that at the species level, A. muciniphila showed a tendency to increase in the Db + dapa group compared to the Db group. A. muciniphila has been shown to improve metabolic outcomes, including vascular function (Qin et al, 2012;Li et al, 2016), while participating in the protection of the intestinal mucosal barrier and controlling low-grade inflammation (Chelakkot et al, 2018;Lee et al, 2019;Tang et al, 2019).…”
Section: Sodium Glucose Co-transporter 2 Inhibitors (Sglt2i)mentioning
confidence: 99%
“…Table 3 lists their details and the involved types of gut microbiota. Not only that, with the participation of gut microbiota, other fields have gradually revealed the role of metformin, including anti-inflammatory effects, downregulation of interleukin expression, and ameliorating polycystic ovary syndrome in an animal model[ 44 ]. Moreover, metformin accelerated fatty acid oxidation by regulating host metabolism and longevity under the action of regulating a multipressure metabolic system[ 43 ].…”
Section: Metformin-gut Microbiota–crc Axis In T2dmmentioning
confidence: 99%
“…In terms of regulating inflammation, after the mice were treated with metformin, the level of inflammatory markers TNF-α, IL-6, and IL-17α in plasma was reduced with a corresponding increase of the level of IL-10, which was accompanied by a reduction in Helicobacter pylori . Lee et al [ 44 ] suggested that fecal microbiota transplantation using metformin-treated mouse fecal material can upregulate the expression of GLP-1 and pattern recognition receptors TLR1 and TLR4. It has been shown that CRC-enriched genotoxic polyketide synthase ( pks ) + E. coli , E. faecalis , and A. finegoldii and TLR2 and/or TLR4 pathway-related bacteria, such as F. nucleatum and Peptostreptococcus anaerobius , are related closely to intestinal inflammation[ 55 ].…”
Section: Underlying Involved Mechanismsmentioning
confidence: 99%